Laboratory profile of HIV-1 and dual HIV-1/HIV-2 associaed acquired immunodeficiency sydrome in Nigeria (2013)
" Background: HIV-2 is comparatively less pathogenic with slow progression of infection to clinical disease and consequently there is less of information on the occurrence of HIV-2 associated disease than HIV-1. We hereby describe some laboratory profiles of individuals presenting with HIV-2 and dual HIV-1/2 related AIDS at the University College hospital in Ibadan over a period of seven years. Methodology: Blood samples from patients presenting with the AIDS defining illness at the University College Hospital, Ibadan, Nigeria were tested for antibodies to HIV-1/2 using rapid test devices or ELISA. Initially reactive samples were further tested by immunoblotting for differentiation into HIV-1 or HIV-2 or HIV-1/2 dual infection. Blood samples from individuals with confirmed infections were further analyzed for CD4 cell lymphocyte number, plasma HIV-1 RNA concentration, hematological and blood chemistry parameters. The data analysis was done using descriptive statistics and Levene-S test for equality of variance. Results: Thirty five patients, 18 and 17 with HIV-2 and dual HIV-1/2 infections respectively were identified during the period covered by this study (2005-2012). The median age of the patients was 48 years old (Range: 42 - 70 years old) and mean CD4 cell count of HIV-2 patients at enrollment was 324 (Range: 16 - 696) and 350 (Range 54 - 863) per microlitre of blood for patients with dual HIV-1/2 infection. HIV-1 RNA was not detected in the plasma of the 18 patients with serological HIV-2 infection but 2 (11.8%) of the 17 patients with dual HIV-1/2 serological profile had detectable HIV-1 RNA (1,287,275 copies/ml and 1,816,491 copies/ml). Conclusion: The results emphasize the need to consider HIV-2 infection in the investigation of patients presenting with the AIDS related illness but with negative HIV-1serology. The study also shows the importance of inclusion of multispot HIV-1 and 2 rapid tests for differentiating HIV-1 from HIV-2 infections in regions where both types of HIV circulate or epidemiologically indicated. "